The Sedimentary records of the Hapcheon impact crater basin in Korea over the past 1.3 Ma - Lee, Jin-Young; Shin, Seungwon; Yoon, Hyun Ho; Kim, Jin Cheul; Choi, Yire; Nahm, Wook-Hyun; Kim, Heejung (Frontiers in Earth Science, 2023)
The Hapcheon Impact Crater (HIC), the only meteorite impact zone identified in Korea, is especially noted by many researchers. However, the morphology of the impact crater was un-known because only the meteorite collision was confirmed so far, and there was no more in-formation on the meteorite collision situation. In the first step, we analyzed sedimentary facies using grain size distribution, sediment core CT images, 14C radiocarbon, 10Be, and OSL dating on recovered over 66 m long 20HCL04 sediment cores from the Hapcheon basin (HB). Four units and ten types of facies were analyzed from the HB sediment cores. The sedimen-tary units consisted of a lower part (unit 1) with dominant moderate to well-sorted coarse gravel, including the amount of impact-related sediments, a middle part (unit 2, unit 3) with dominant mud with well-developed laminar and bedding, and an upper part (unit 4) with dominant poorly sorted coarse gravel supplied from the mountain slope transported by the alluvial and fluvial process. After the meteorite collision, the deposition layer of HIC was filled with deposits sup-plied from the crater wall after ca. 1.3 Ma in the crater of HB and changed into a deep lake en-vironment. After ca. 0.5 Ma, sediments began to be supplied through the surrounding mountains in HB until the lake collapsed. Finally, the sediments of the alluvial fan remain at present. In addition, the HB sedimentary records, including the tephra layer and soft deformed sedi-ments (SSDS) for understanding volcanic and seismic activities, confirm that important infor-mation can be provided for research on the paleo-environments of the Korean Peninsula after 1.3 Ma.